ANALYSIS OF FACTORS AFFECTING THE EMPLOYMENT OPPORTUNITIES OF WOMEN IN THE FORMAL SECTOR IN DENPASAR CITY - Putu Ayu Mas Saty Devi; Ida Ayu Nyoman Saskara (INJOSEDU: International Journal of Social and Education, 2025)
Gender inequality in the workplace remains a significant issue in Indonesia, including in Denpasar. Although the formal sector offers greater stability and legal protection, women often face challenges such as wage disparities, limited career mobility, and disproportionate domestic responsibilities. Nevertheless, women's participation in the formal sector is crucial in promoting inclusive economic development, particularly in relation to gender equality as outlined in the Sustainable Development Goals (SDGs). This study aims to evaluate various factors including age, husband's income level, number of dependents, and educational attainment affecting the participation of married women in formal employment in Denpasar City. A binary logistic regression model was employed as the quantitative approach in this research. Primary data were collected through purposive sampling of 70 married women, both those employed and unemployed in the formal sector. Secondary data were obtained from the Denpasar City Central Statistics Agency (BPS). The findings reveal that educational attainment and husband's income significantly influence women's likelihood of working in the formal sector; education has a positive effect, while age has a negative impact. The number of dependents in the household was found to have no significant effect. These results highlight the need for policies that support women’s education, skills training, and flexible working arrangements in order to enhance female labor force participation in urban areas.